Short communication: Biochemically active humic substances in contrasting agricultural managements - Benitez, Emilio; Nogales, Rogelio; Doni, Serena; Masciandaro, Grazia; Moreno, Beatriz (Spanish Journal of Agricultural Research, 2016)
Because their crucial role in several soil biochemical cycles and their fast response to changes in soil management, extracellular enzymes activities are widely used as sensitive indicators of ecological change and soil quality. The aim of this work was to determine the effects of soil management on the stable pool of soil carbon cycling enzymes as indicators of essential functions. For this, extracellular β-glucosidase enzymes bounded by humic acids (C higher than 104 Da) were used to compare four long-term contrasting agricultural managements in a rainfed olive orchard representative of semi-arid Mediterranean habitats. The study was conducted for 30 years by designing a random-block of four treatments (nude vs. covered soils) and four replicates. Maintaining cover crops through fall, winter and early spring provoked a more stable and active pool of extracellular β-glucosidase in soils only if spontaneous vegetation was managed with mechanical methods. When herbicides were used during 30 years, the pattern of the molecular composition and activity of humus β-glucosidase complexes were similar in covered and nude soils, although higher activity was retrieved in the former. Tillage management increased carbon mineralization and the level of humic substances and the activity of β-glucosidase humic-bound were quite lower than in the rest of treatments. Given the ecological role of extracellular soil carbon cycling enzymes, the characterization of humus β-glucosidase complexes could be an adequate indicator of sustainability of agricultural management systems.